MIS 5–1 dinoflagellate cyst analyses and morphometric evaluation of Galeacysta etrusca and Spiniferites cruciformis in southwestern Black Sea. (20th January 2018) - Ferguson, Shannon; Warny, Sophie; Escarguel, Gilles; Mudie, Petra J.
Abstract: Here we evaluate the changes in dinoflagellate cyst assemblages and intraspecies morphometric variability in dominant Black Sea species during MIS 5−1 in sediment recovered from DSDP Site 380. Twenty-three taxa represent the majority of the 16, 000 cysts tabulated. Qualitative assessment of assemblage composition indicates that the taxa are distributed in three ecological assemblages; marine stenohaline, marine euryhaline, and brackish Ponto-Caspian endemic species; the fluctuation of these assemblages provide evidence for changes in environmental conditions from the end of MIS 5e to MIS 1. Although some fluctuations in sea-surface salinity are highlighted by changes in dinoflagellate assemblages, the continuous presence of Pyxidinopsis psilata, Galeacysta etrusca and Spiniferites cruciformis likely indicate brackish conditions for most of the interval sampled at this site. Statistical analysis of measured morphometric changes in Galeacysta etrusca endocyst:ectocyst ratios indicate that the specimens recovered mostly belong to a smaller morphotype forming group 'b' of Popescu et al. (2009), interpreted as indicative of brackish–marine conditions after migration to the Mediterranean from the Paratethys. Although not fully conclusive because of sampling constraints and limited chronological control, the lack of sudden, large abundance changes in marine salinity-tolerant species the relatively low species diversity, and the sequence of sapropelic layers relative to banded clastic muds provides evidence against the occurrence of sustained marine flooding between ca. 0.07–0.007 Ma and it is not clear that the last interglacial marine highstand during MIS 5e was fully sampled at this site.